A conserved clathrin‐coated vesicle component, OsSCYL2, regulates plant innate immunity in rice. (21st December 2021) - Yao, Yao; Zhou, Jihua; Cheng, Can; Niu, Fuan; Zhang, Anpeng; Sun, Bin; Tu, Rongjian; Wan, Jianing; Li, Yao; Huang, Yiwen; Xie, Kaizhen; Dai, Yuting; et al.
Abstract: Clathrin‐mediated vesicle trafficking (CMVT) is a fundamental process in all eukaryotic species, and indispensable to organism's growth and development. Recently, it has been suggested that CMVT also plays important roles in the regulation of plant immunity. However, the molecular link between CMVT and plant immunity is largely unknown. SCY1‐LIKE2 (SCYL2) is evolutionally conserved among the eukaryote species. Loss‐of‐function of SCYL2 in Arabidopsis led to severe growth defects. Here, we show that mutation of OsSCYL2 in rice gave rise to a novel phenotype—hypersensitive response‐like (HR) cell death in a light‐dependent manner. Although mutants of OsSCYL2 showed additional defects in the photosynthetic system, they exhibited enhanced resistance to bacterial pathogens. Subcellular localisation showed that OsSCYL2 localized at Golgi, trans‐Golgi network and prevacuolar compartment. OsSCYL2 interacted with OsSPL28, subunit of a clathrin‐associated adaptor protein that is known to regulate HR‐like cell death in rice. We further showed that OsSCYL2–OsSPL28 interaction is mediated by OsCHC1. Collectively, we characterized a novel component of the CMVT pathway in the regulation of plant immunity. Our work also revealed unidentified new functions of the very conserved SCYL2. It thus may provide new breeding targets to achieve both high yield and enhanced resistance in crops. Summary Statement: This study shows that OsSCYL2, a eukaryotic conserved SCY1‐LIKE kinase, interacts with the medium subunit μ1 of clathrin‐coated adaptor protein complex 1 (OsSPL28) via clathrin heavy chain 1, and regulates plant immunity and cell death in rice. These results shed new insights into the clathrin‐mediated vesicle trafficking‐mediated signalling pathway in the regulation of plant immunity, and therefore may provide new breeding targets to achieve both high yield and enhanced resistance in crops.